2024
DOI: 10.3233/jad-230573
|View full text |Cite
|
Sign up to set email alerts
|

What Does ChatGPT Know About Dementia? A Comparative Analysis of Information Quality

Jill A. Dosso,
Jaya N. Kailley,
Julie M. Robillard

Abstract: The quality of information about dementia retrieved using ChatGPT is unknown. Content was evaluated for length, readability, and quality using the QUEST, a validated tool, and compared against online material from three North American organizations. Both sources of information avoided conflicts of interest, supported the patient-physician relationship, and used a balanced tone. Official bodies but not ChatGPT referenced identifiable research and pointed to local resources. Users of ChatGPT are likely to encoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The primary aim was to replicate the search behavior of a novice user engaging with ChatGPT for the first time and to assess the quality of the material retrieved from the Large Language Model in comparison to publicly available resources from Alzheimer’s disease-related organizations in North America. The study's findings indicated that users interacting with ChatGPT are likely to access accurate yet superficial information concerning dementia 41 .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The primary aim was to replicate the search behavior of a novice user engaging with ChatGPT for the first time and to assess the quality of the material retrieved from the Large Language Model in comparison to publicly available resources from Alzheimer’s disease-related organizations in North America. The study's findings indicated that users interacting with ChatGPT are likely to access accurate yet superficial information concerning dementia 41 .…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, numerous studies evaluating ChatGPT's performance in medical domains have consistently shown its unreliability in providing clinical information, particularly regarding chronic diseases 36 38 , 41 , 42 . Consequently, at present, it appears to be more suitable for addressing basic inquiries, such as those unrelated to clinical aspects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Hristidis et al (2023) compared ChatGPT with Google search for questions specifically related to dementia and cognitive decline with subpar quality for both systems. In line with this, ChatGPT's knowledge of dementia has been designated as "accurate but shallow" (Dosso et al, 2023). This can potentially be alleviated by finetuning LLMs on medical data.…”
Section: Information Retrievalmentioning
confidence: 99%